Feasibility and Preliminary Effects of a 1-Week Vestibular Rehabilitation Day Camp in Children with Developmental Coordination Disorder. (1st December 2021) - Dannenbaum, Elizabeth; Bégin, Caro-Lyne; Daigneault-Bourgeois, Éliane; Kwon Pak Yin, Nancy; Laferrière-Trudeau, Chloé; Mazer, Barbara; Moreau, Virginie; Salvo, Lora; Villeneuve, Myriam; Lamontagne, Anouk
Abstract: Aim: This pilot study investigated the feasibility and preliminary effects of an intensive 1-week day camp program for children with Developmental Coordination Disorder (DCD) that focused on vestibular rehabilitation. Methods: Ten participants (6-10 years) were assessed twice pre-intervention, post intervention, and at 8-week follow-up. Videonystagmography, Video Head Impulse Tests (vHIT), and Modified Emory Clinical Vestibular Chair Test (m-ECVCT) test were assessed at baseline. Outcomes measures were gaze stability (Dynamic Visual Acuity; DVA), functional gait (Functional Gait Assessment; FGA), balance (Sensory Organization Test), motor function (Bruininks-Oseretsky Test), and participation (Miller Function and Participation). Results: No abnormal results were detected from the videonystagmography, vHIT and m-ECVCT. There was a 100% attendance rate at the camp and assessment sessions. FGA scores significantly improved following intervention and changes were maintained at follow-up. The number of children with abnormal DVA scores decreased from 3 to 1 to 0 between pre-intervention, post-intervention, and follow-up. There were no significant changes in any of the other outcomes following intervention. Conclusions: Intensive vestibular rehabilitation delivered in a day camp format is feasible and show positive preliminary effects on functional gait and dynamic visual acuity in children with DCD.